(untitled) (Biological Sciences - PJSIR, 2006)
The study aimed at providing a low-cost treatment for brewery wastewater, which was achieved by mixing clay with stone-pebbles to improve the low permeability of water through clay beds. The combination (clay/stone-pebbles) was used in columns for the treatment of brewery wastewater . The crystal chemistry of the clay samples was studied using X-ray diffractometer. Three principal clay minerals (kaolin, illite and smectite) were detected in the samples. Atomic absorption spectrophotometer was used to study the geochemistry of the clay samples. The results of the geochemical studies showed that all the samples were hydrated aluminosilicates. Performance efficiency studies were conducted to determine the best combination ratio of clay to stone-pebbles, which showed that combination ratio 3:1 (clay/stone- pebbles, w/w) performed better. The flow-rate studies showed that brewery wastewater had longer residence time in non- fortified clay than in fortified clay. The flow-rate of the wastewater in the percolating media varied from one medium to another. Two modes of treatment (batch and continuous) were used. The effluent passed through the continuous treatment mode had better quality characteristics as compared with the effluent passed through the batch treatment mode. The effect of repeated use of the fortified column on the performance efficiency was also studied. The pH, total solids, and the chemical oxygen demand (COD) of the effluent was monitored over time. The results of the COD monitored over time were analysed using breakthrough curves. The different columns were found to have different bed volumes at both the break- through and exhaustion points.